FAKTOR FUNDAMENTAL EKONOMI MAKRO TERHADAP HARGA SAHAM LQ45 - I Gusti Ayu Purnamawati; Desak Nyoman Sri Werastuti (University of Merdeka Malang, 2013)
The capital market was an important element that provided benefits for the economic progress through invest-ment development in a country. LQ45 index was the list of 45 excellent chosen stocks 45 which were the mostliquid and most active in the sale of the shares on the Stock Exchange. This study aimed to determine the effectof macroeconomic fundamentals on LQ45 stock price. The population used in this study was LQ45 shares inIndonesia Stock Exchange in 2007-2012. The method used in this study was the Error Correction Model(ECM). The dependent variable in this study was the stock price of LQ45, while the independent variables werethe rate of economic growth, inflation, the value of U.S. dollar against rupiah exchange rate, and SBI interestrate. The results showed that the rate of economic growth and a variable SBI interest rate had a negative effectin the short-term and long-term of LQ45 stock price. Inflation variable had a positive effect in the short-termand long-term of LQ45 stock price. While the exchange rate variable had a negative effect in the short-term andit had positive impact in long-term on the LQ45 stock price.